Comparison of Cultural Competence Between Dental House Officers and General Dentists: A Cross‐Sectional Study - Shaur Sarfaraz; Maria Ghani; Batool Sajjad; Dinaz Ghandhi; Tayyaba Akram; Maria Shakoor Abbasi; Naseer Ahmed; Artak Heboyan (Health Science Reports)
ABSTRACT Background All patients deserve quality care, regardless of their cultural, ethnic, or linguistic backgrounds. In Pakistan's diverse society, cultural competence in dentistry is crucial for patient‐centered care. This study assesses and compares cultural competence levels between dental house officers (DHOs) and general dentists (GDs). Methods A cross‐sectional, self‐reported study was conducted at Altamash Institute of Dental Medicine, Karachi, over 6 months. A validated questionnaire (α = 0.856) on a 4 to 5‐point scale assessed five attributes via Google forms. Data were analyzed using SPSS 23. Independent Sample t‐test was used to compare DHOs and GDs, while ANOVA evaluated differences in GDs' qualification and practice settings. Results A total of 316 participants (response rate: 79%) were included. The mean age was 24.77 ± 2.02 years for DHOs and 31.32 ± 7.49 years for GDs. Females were predominant, and 27% of GDs worked in private practice. Both groups were somewhat culturally competent, with DHOs showing significantly higher self‐perception (2.09 ± 0.61 vs. 1.92 ± 0.26, p = 0.001). However, GDs scored slightly higher in patient‐centered communication, practice orientation, and cultural competence behaviors. GDs in private practice were more culturally competent than those working only in OPDs (−0.274*, F: 3.542, p = 0.001). Conclusion Overall, participants perceived themselves as somewhat culturally competent. DHOs demonstrated greater self‐awareness and sensitivity than GDs. GDs in training and private practice exhibited higher cultural competence than those in OPDs alone.